2019
DOI: 10.1016/j.jalz.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F‐florbetaben quantification results using the standard Centiloid, MR‐based, and MR‐less CapAIBL® approaches: Validation against histopathology

Abstract: Introduction18F‐florbetaben is currently approved for the visual rule out of β‐amyloid (Aβ) pathology. It is also used for recruitment and as an outcome measure in therapeutic trials, requiring accurate and reproducible quantification of Aβ burden in the brain.MethodsData from eighty‐eight subjects (52 male subjects, aged 79.8 ± 10.6 years) who underwent antemortem 18F‐florbetaben positron emission tomography scan and magnetic resonance imaging less than a year before neuropathological assessment at autopsy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 29 publications
2
43
0
1
Order By: Relevance
“…This is reasonably concordant with the findings of Navitsky and colleagues, who determined a threshold of 24.1 CL with florbetapir for CERAD amyloid plaque classification of moderate or frequent vs sparse or none, in 59 individuals [22]. This is also concordant with the Centiloid analysis by Dore and colleagues of a florbetaben phase III post-mortem study in 66 individuals, which yielded a threshold of 19 CL for the same categorisation [23]. These thresholds are higher than those identified by La Joie et al, who determined a threshold of 12.2 CL for separating none or sparse plaques from moderate or frequent plaques; but oddly they found the same threshold for separating any plaques from no plaques in 179 individuals scanned with 11 C-PiB PET [21].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is reasonably concordant with the findings of Navitsky and colleagues, who determined a threshold of 24.1 CL with florbetapir for CERAD amyloid plaque classification of moderate or frequent vs sparse or none, in 59 individuals [22]. This is also concordant with the Centiloid analysis by Dore and colleagues of a florbetaben phase III post-mortem study in 66 individuals, which yielded a threshold of 19 CL for the same categorisation [23]. These thresholds are higher than those identified by La Joie et al, who determined a threshold of 12.2 CL for separating none or sparse plaques from moderate or frequent plaques; but oddly they found the same threshold for separating any plaques from no plaques in 179 individuals scanned with 11 C-PiB PET [21].…”
Section: Discussionsupporting
confidence: 89%
“…Three recent studies have examined the performance of amyloid PET CL thresholds compared with SoT neuropathology. These studies reported thresholds for detection of moderate or frequent neuritic plaque ranging from 12 to 24 CL but did not correct for time elapsed between amyloid scan and death and had relatively few cases with CL values close to the threshold values [21][22][23]. Only one compared to Alzheimer's disease neuropathologic change (ADNC) rating [1] or to expert visual read report of a positive scan [21].…”
Section: Introductionmentioning
confidence: 99%
“…This is reasonably concordant with the findings of Navitsky and colleagues, who determined a threshold of 24.1 CL with florbetapir for CERAD amyloid plaque classification of moderate or frequent vs sparse or none, in 59 individuals [21]. This is also concordant with the Centiloid analysis by Dore and colleagues of a florbetaban phase III post-mortem study in 66 individuals, which yielded a threshold of 19 CL for the same categorisation [22]. These thresholds are higher than those identified by La Joie et al, who determined a threshold of 12.2 CL for separating none or sparse plaques from moderate or frequent plaques; and the same threshold of 12.2CL for separating any plaques from no plaques in 179 individuals scanned with 11 C-PiB PET [20].…”
Section: Fig 1 Centiloid Results and "High" Vs "Low" C Score Categoriessupporting
confidence: 89%
“…An SUVR abnormality cutoff of 1.478 in a global cortical composite region relative to the cerebellar cortex was developed using histopathological confirmation as the standard of truth providing excellent sensitivity (89.4%) and specificity (92.3%) to detect established Aβ pathology [9]. Other groups have developed other SUVR abnormality cutoffs for 18 F-florbetaben PET ranging from 1.38 to 1.45 using different populations, analytical methods, and standards of truth [10,[12][13][14][15][16][17][18]. These SUVR cutoffs, however, were developed with the aim of discriminating between subjects with established Aβ pathology (e.g., AD) and other populations (e.g., cognitively normal elderly subjects).…”
Section: Introductionmentioning
confidence: 99%